Anals of the faculty of medicine. Towars the National Becenntenial - Garmendia-Lorena, Fausto (2022)
A critical revue of the contents of the journal Anales de la Facultad de Medicina from 2015 to 2020 has been done. It has been quatified and qualified the publicactions of every section under the relevance of one century of its appareance and the National Bicenntenial. The instructions for the authors, its prosprect, norms and clasification of the contents have been taken in account as a basis for this research. There were not found contributions in sections photos gallery nor commensts of books. In the time being 6 volumes, 24 numbers and 2 especial numbers were edited. In a half of the first numbers editorials lack of titels. An amount of 144 original articles, 44 short originals, 26 reviews, 34 special artícles, 14 on history, 3 simposia, 49 clinical cases, 79 letters to editors, 12 guides were published. In relation to the themes, the majority were on medicine and subspecialties. Basic science articles 16, general and experimental surgery 8, pediatricians 4, gineco-obstetrics 13, quality of health services 25, public health 20, health education 16, research methodology and occupational diseases 6 every one, miscelánea 29. Forein and representatives of international agencies contributed in 73 artícles. It is concluded that Anales de la Facultad de Medicina is a scientific journal with a wide tradition, indexed, emblematic of the Faculty of Medicine with national and international significance.